Influence of Family Support for Antipsychotic Treatment Adherence in Schizophrenic Patients - Ika Ratna Hidayati; Lina Fitrianidiah; Liza Pristianty (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2021)
Schizophrenia is a psychosis disorder characterized by confusion in mind and personality in form of regression, hallucinations, delusions and withdrawal from the environment. One of the managements of schizophrenia is antipsychotic treatment. Antipsychotic treatment must be regular and given for long-term to provide a therapeutic effect and prevent relapses. This study used an analytic observational method with cross-sectional approach, questionnaire was used as an instrument. Sampling was done by purposive sampling method based on inclusion criteria, then the data were analyzed using the Chi-Square method to determine the influence of family support and treatment adherence by SPSS program. The results showed from 30 respondents, 21 respondents (70%) obtained good support and 9 respondents (30%) had poor support. And the result on adherence, 16 respondents (53.33%) adherent, while 14 respondents (46.67%) did non-adherent. Based on the results of this study, it was concluded that there was an influence between family support and adherence to antipsychotic treatment in schizophrenic patients at Bantur Health Center, Malang Regency. The results of the Chi-Square test analysis with a df value of 3,841 (df = 1) obtained P - Value 10,049> 3,841 or a significance value of 0.004 <0.05 (5%).